NILAI TAMBAH DAN SALURAN PEMASARAN IKAN JULUNG-JULUNG (Hemirhamphus Sp) ASAP DI DESA BUAJANGKA KECAMATAN BUNGKU SELATAN KABUPATEN MOROWALI PROVINSI SULAWESI TENGAH - Ahsan Mardjudo; Ade Ayu (Jurnal Pengolahan Pangan, 2019)
This research aims to find out the fumigation process (local: roa fish)and the added value of fumigation processing, and knowing the marketing channels for roa fish in Buajangka village, South Bungku District of Morowali regency in Central Sulawesi Province. Data collection in this research was carried out by census method to all people who conduct fumigation of smoked-baffled fish (roa fish) in Buajangka Village. The data were analysis through qualitative and quantitative descriptive approaches. The research results show that technically, the fumigation process for roa fish starts from receiving raw materials, washing, transporting, clamping and fixing clips, structuring, fumigation process, and packaging or packing. The added value generated from the cocoa fumigation business in Buajangka Village, South Bungku District in per bunch of roa fish is Rp. 6,082. The added value generated from the cocoa fumigation business in the study area was relative low with a value added ratio> 50% (40.54%). While the marketing channel of Roa's fish fumigation business sells smoked roa fish products directly to consumers and collectors who come from outside the region such as Kendari, Bungku Tengah, Tentena, Poso and Palu who come directly to the place of roa fumigation.